Autumn migration of the Wood Sandpiper (Tringa glareola) in the southern Belarus (Pripyat Floodplain) - Pinchuk, P.V. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2003)
The paper presents a preliminary analysis on the Wood Sandpiper autumn migration across the Pripyat floodpain in southern Belarus during 1998-2001. A total of 103 counts were conducted, and 1653 Wood Sandpipers were counted in the vicinity of Turov village. A total of 125 juveniles and 14 adults were captured during the autumn migration in 1999-2001. The most complete counts were carried out in 2000. В статье представлен предварительный анализ осенней миграции фифи в пойме р.Припятъ на юге Беларуси в 1998-2001 гг.. В 1998-2000 гг. проведено 103 маршрутных учета и учтено 1653 птицы в р-не с.Туров. На осеннем пролете в 1999-2001 гг. отловлено 125 молодых и 14 взрослых птиц. В наиболее полном объеме учеты были проведены в 2000 г. У статті представлено попередній аналіз осінньої міграції коловодника болотяного в заплаві р. Прип’ять на півдні Білорусі в 1998-2001 рр. У 1998-2000 рр. проведено 103 маршрутних обліки, у ході яких нараховано 1653 птахи в районі с. Туров. Під час осіннього прольоту в 1999-2001 рр. відловлено 125 молодих та 14 дорослих птахів. Найбільш повний облік було проведено у 2000 р.